Some molecular aspects of larval development in Paralithodes camtschaticus - Alexey V. Boyko; Igor Yu. Dolmatov; Alexander S. Girich; Sergey I. Maslennikov (PLoS ONE, 2025)
The transcriptome of the red king crab, Paralithodes camtschaticus , was sequenced at four developmental stages: zoea I, zoea IV, glaucothoe, and juveniles. Based on our RNA-seq data and paired-end reads from 112 libraries obtained by other researchers earlier, the transcriptome assembly for P. camtschaticus that we obtained has proven to be the most complete of those reported to date. An analysis of enriched processes at different stages has shown, that some of adaptations, e.g., to elevated temperature and hypoxia, do not appear in early larvae. Thus, it is important to maintain optimal conditions for normal larval development and reduce mortality rates. According to the results of the expression profile clustering and transcription factor (TF) search, most TFs are associated with the development of various organs, metamorphosis, and immune responses. The data obtained provide an additional basis for deeper investigation into the mechanisms of the biphasic life cycle in decapods and can be helpful in commercial red king crab stock enhancement programs.